The Maturation of the Acoustic Change Complex in Response to Iterated Ripple Noise in ‘Normal’-Hearing Infants, Toddlers, and Adults - Strahm, S.; Small, S. A.; Chan, S.; Tian, D. Y.; Sharma, M. (Journal of the American Academy of Audiology, 2022)
Background Infants and toddlers are still being evaluated for their hearing sensitivity but not their auditory-processing skills. Iterated rippled noise (IRN) stimuli require the auditory system to utilize the temporal periodicity and autocorrelate the iterations to perceive pitch.Purpose This study investigated the acoustic change complex (ACC) elicited by IRN in “normal”-hearing infants, toddlers, and adults to determine the maturation of cortical processing of IRN stimuli.Design Cortical responses to filtered white noise (onset) concatenated with IRN stimuli (d = 10 milliseconds, gain = 0.7 dB: 4–32 iterations) were recorded in quiet, alert participants.Study Sample Participants included 25 infants (2.5–15 months), 27 toddlers (22–59 months), and 8 adults (19–25 years) with “normal” hearing sensitivity.Data Collection and Analysis Cortical auditory-evoked responses were recorded for each participant, including the onset response to the noise and an ACC to the transition from noise to IRN. Group differences were assessed using repeated-measures analyses of variance.Results Most infants had a replicable onset (P) response, while only about half had a measurable ACC (PACC) response to the high-saliency IRN condition. Most toddlers had onset responses and showed a P-NACC response to the IRN16 and IRN32 conditions. Most of the toddler group had responses present to the onset and showed a P-NACC response to all IRN conditions. Toddlers and adults showed similar P-NACC amplitudes; however, adults showed an increase in N1ACC amplitude with increase in IRN iterations (i.e., increased salience).Conclusion While cortical responses to the percept of sound as determined by the onset response (P) to a stimulus are present in most infants, ACC responses to IRN stimuli are not mature in infancy. Most toddlers as young as 22 months, however, exhibited ACC responses to the IRN stimuli even when the pitch saliency was low (e.g., IRN4). The findings of the current study have implications for future research when investigating maturational effects on ACC and the optimal choice of stimuli.
Keywords: acoustic change complex; iterated rippled noise; children; maturation